Cost efficiency evaluation for a two-stage series network in data envelopment analysis - Zohreh Moghaddas; Mohsen Vaez Ghasemi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Cost efficiency evaluation in a network system using data envelopment analysis models can be improved from various aspects in real-world applications. This study aims to consider a specific set of weights for cost-efficiency assessment in a two-stage network system. Methodology: Using the data envelopment analysis technique, we tried to provide a model for the cost evaluation of a network system. Findings: Considering the relations among different stages in a network system can directly affect the obtained results. This issue is investigated from cost efficiency evaluation. Considering the set of weights from various aspects can affect the obtained scores. Originality/Value: According to the models and methods in the DEA literature, a model is presented to consider cost efficiency in a two-stage DEA model in this study.